VIRAL CIRRHOSIS: AN OVERVIEW OF HAEMOSTATIC ALTERATIONS AND CLINICAL CONSEQUENCES - Francesca Romana Ponziani; Valerio De Stefano; Antonio Gasbarrini (Mediterranean Journal of Hematology and Infectious Diseases)
Viral hepatitis is a major health problem worldwide, the principal cause of cirrhosis and hepatocarcinoma. Once cirrhosis occurs, the consequences of liver dysfunction and portal hypertension become evident and, sometimes, life threatening for patients. Among the various complications of liver cirrhosis, the alteration of haemostatic balance is often a hard challenge for the clinician, since it is capable to predispose both to bleeding or thrombosis. In this review, we analyze the principal aspects of procoagulant, anticoagulant and fibrinolytic capacity of cirrhotic patients, which appears to be variably altered in all these aspects, not only in the direction of a tendency to bleeding. Laboratory investigations, at present, may provide only a partial representation of this condition, because of the impossibility to obtain a test capable to furnish a global overview of the haemostatic system and to reproduce in vivo conditions. Furthermore, we describe the pathophysiological mechanisms underlying bleeding manifestations and thrombosis development in cirrhotic patients,  which should be considered not only as obvious consequences of the advanced liver disease but, rather, as the result of a complex interaction between inherited and acquired factors.